(untitled) (GIST – Education and Learning Research Journal, 2016)
This paper examines the phonemic realisations of the letter <Ii> and <Yy> in Educated Nigerian English Accent (ENEA) as a second language. It is based on the concept of intraference. Examples were gathered from 2005 to 2013 in a national survey through interviews, participant observation and the recording of spontaneous speeches. The method of analysis is eclectic: qualitative textual analysis and description, and quantitative statistical presentation of data. Ordinal data are presented in percentile and frequency tables and charts and the linguistic texts are described, explained and compared with RP variants. The study established that educated Nigerians redeploy the various British RP realisations of the letters and <y> indiscriminately to pronounce words in which the letters appear in a manner that RP and other native English accents may not pronounce them, thereby producing phonological variants. Since the variants emanate from the (un)conscious redeployment of underlying RP phonemic realisations of the letters and since they are institutionalised in ENE, the paper proposes that they be treated as variations that characterise ESL and Educated Nigerian English Accent (ENEA).